Inclusive community playgrounds benefit typically developing children: An objective analysis of physical activity - Stevens, Wilshaw R.; Borchard, Justine M.; Sleeper, Paige; Dempsey, Dana; Jeans, Kelly A.; Jo, Chan-Hee; Tulchin-Francis, Kirsten (Frontiers in Sports and Active Living, 2023)
Purpose Limited research is available on the physical activity levels of children while playing on an inclusive playground, specifically designed to accommodate children with physical disabilities. The aims of this study were to objectively measure ambulatory activity and heart rate (HR) of children during unstructured play on an inclusive community playground. Methods Typically developing children at least 4 years of age were recruited to play freely upon entering the playground. Participants wore a StepWatch4 Activity Monitor and a Polar V800 Sport Watch. Ambulatory measures included total steps, percentage of recommended steps, total ambulatory time (TAT), bout intensity levels/duration periods. Time spent in HR zones and moderate-to-vigorous physical activity (MVPA) was determined. Results 95 children (48 males; Avg. age: 7±2 yrs.) were included in this study. Children played for 31.8±14.7 min., were ambulatory for 25.9±12.0 min., took 1826±824 steps, and accumulated 17±8% of the recommended daily step count. Ambulatory bout intensity was predominantly lower intensity and bout durations varied in length. 99% of the play time was spent at a moderate HR or higher. Significant correlations were found between ambulatory and HR measures (ρ range from 0.23 to 0.99, p<0.05), and 7-10 yo children spent a significantly higher percentage of TAT at higher intensity ambulation (p<0.05). Conclusions Typically developing children can achieve moderate or higher intensity exercise and HR on an inclusive playground. Both typically developing children and those with disabilities, would benefit from a setting where they can interact and participate in parallel play with their peers.